Country Calls: A Creative Practice of Deep Time Walking in Darug Country. (June 2022) - Somerville, Margaret J.
This article presents my personal story, as a non-Indigenous settler woman, of walking along a ridge close to my home at the foot of the Blue Mountains west of Sydney, after the fires of 2019 to 2020. In this article, I want to invite the reader into my love of this country through sharing my record of this walking over a 12-month seasonal cycle. Every walk presented me with new understandings of this Country where I live, which I already knew as Darug Country, having explored the nature of this country in collaboration with my Darug friends Jacinta and Leanne Tobin.